Olympic Volunteers, a Sociological Phenomenon of Modern Sports - Castellanos, Douglas Crispín; Ucha, Francisco Garcia; Truan, Juan Carlos Fernández; Prendes, Juan J. Alfonso (European Scientific Journal, ESJ, 2014)
This research is aimed to evaluate from a sociological point of view the Olympics volunteers’ phenomenon, a movement by which those so famous and followed summer and winter Olympic Games couldn´t be held, likewise; those special, Paralympics and Youth Games couldn´t be held either. We used the documentary analysis and historical logical methods to carry out the investigation; being its greatest contribution the evaluation of the Olympic volunteer’s socio-psychological characteristics and the socio-political and economical environment they live in, which allow them to take part in these international competitions of a greater magnitude. This work labels and identifies the volunteers taking into consideration the role they play during the contests and makes a proposal for a way of contribution to make internationally wider the Olympic ideal through the Olympic volunteers´ phenomenon.